Functional, morphological and electrocardiographical abnormalities in patients with apical hypertrophic cardiomyopathy and apical aneurysm: correlation with cardiac MR. Issue 1 (13th August 2014) - Suwa, Kenichiro; Satoh, Hiroshi; Sano, Makoto; Nobuhara, Mamoru; Saitoh, Takeji; Saotome, Masao; Urushida, Tsuyoshi; Katoh, Hideki; Tawarahara, Kei; Ohtani, Hayato; Wakabayashi, Yasushi; Takase, Hiroyuki; et al.
Abstract : Objective: The prognosis of apical hypertrophic cardiomyopathy (APH) has been benign, but apical myocardial injury has prognostic importance. We studied functional, morphological and electrocardiographical abnormalities in patients with APH and with apical aneurysm and sought to find parameters that relate to apical myocardial injury. Methods: Study design : a multicentre trans-sectional study. Patients : 45 patients with APH and 5 with apical aneurysm diagnosed with transthoracic echocardiography (TTE) in the database of Hamamatsu Circulation Forum. Measure : the apical contraction with cine-cardiac MR (CMR), the myocardial fibrotic scar with late gadolinium enhancement (LGE)-CMR, and QRS fragmentation (fQRS) defined when two ECG-leads exhibited RSR's patterns. Results: Cine-CMR revealed 27 patients with normal, 12 with hypokinetic and 11 with dyskinetic apical contraction. TTE misdiagnosed 11 (48%) patients with hypokinetic and dyskinetic contraction as those with normal contraction. Apical LGE was apparent in 10 (83%) and 11 (100%) patients with hypokinetic and dyskinetic contraction, whereas only in 11 patients (41%) with normal contraction (p<0.01). Patients with dyskinetic apical contraction had the lowest left ventricular ejection fraction, the highest prevalence of ventricular tachycardia, and the smallest ST depression and depth of negative T waves. The presence of fQRS was associated with impaired apical contraction and apical LGE (OR=8.32 and 8.61, p<0.05). Conclusions: CMR is superior to TTE for analysing abnormalities of the apex in patients with APH and with apical aneurysm. The presence of fQRS can be a promising parameter for the early detection of apical myocardial injury.